â€œI can Speak Like You, I am Just Differentâ€ A Psycholinguistics Study of Autistic Child - Dyah Ayu Rahmawati; Emy Sudarwati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Language deficiency is one of the barriers that autistic children face in their language growth. Autistic children may face these difficulties in which they have trouble in understanding and communicating their language. Using Chaer's Language Disorders Theory (2003), this research attempts to investigate the receptive language disorders performed by an autistic child named Rahesa and the expressive language disorders performed by an autistic child named Rahesa based on Suhermanâ€™s (2016) theory. Using a qualitative with descriptive approach, the data were taken from the videos of the subjectâ€™s relationship with his mother, then transcribed into dialogs and analyzed. Then, researcher continued to describe all the findings. The findings of this research indicate that an autistic person has trouble interpreting the message of others and communicating his/her emotions by verbal words. An autistic boy has three difficulties with receptive language disorder, such as difficulty in interpreting verbal language, difficulty in following verbal guidance, and difficulty in focusing his mind.As far as expressive language disorder is concerned, an autistic person faces six difficulties, such as difficulty in inserting words into sentences, difficulty in choosing the correct expression, poor comprehension, taking words out of sentences, repeating some words or phrases, and inappropriately using language structure.The present thesis seeks to offer insights to prospective scholars who are interested in linguistic, in particular psycholinguistics concerned with language problems in the case of autism. General readers will enrich their understanding of and how to cope with the forms of language problems in autistic children.